Fixed Compared With Autoregulation-Oriented Blood Pressure Thresholds After Mechanical Thrombectomy for Ischemic Stroke. Issue 3 (March 2020) - Petersen, Nils H.; Silverman, Andrew; Strander, Sumita M.; Kodali, Sreeja; Wang, Anson; Sansing, Lauren H.; Schindler, Joseph L.; Falcone, Guido J.; Gilmore, Emily J.; Jasne, Adam S.; Cord, Branden; Hebert, Ryan M.; et al.
Abstract : Background and Purpose—: Loss of cerebral autoregulation in the acute phase of ischemic stroke leaves patients vulnerable to blood pressure (BP) changes. Effective BP management after endovascular thrombectomy may protect the brain from hypoperfusion or hyperperfusion. In this observational study, we compared personalized, autoregulation-based BP targets to static systolic BP thresholds. Methods—: We prospectively enrolled 90 patients undergoing endovascular thrombectomy for stroke. Autoregulatory function was continuously measured by interrogating changes in near-infrared spectroscopy–derived tissue oxygenation (a cerebral blood flow surrogate) in response to changes in mean arterial pressure. The resulting autoregulatory index was used to trend the BP range at which autoregulation was most preserved. Percent time that mean arterial pressure exceeded the upper limit of autoregulation or decreased below the lower limit of autoregulation was calculated for each patient. Time above fixed systolic BP thresholds was computed in a similar fashion. Functional outcome was measured with the modified Rankin Scale at 90 days. Results—: Personalized limits of autoregulation were successfully computed in all 90 patients (age 71.6±16.2, 47% female, mean National Institutes of Health Stroke Scale 13.9±5.7, monitoring time 28.0±18.4 hours). Percent time with mean arterial pressure above the upper limit of autoregulation associated with worse 90-day outcomes (odds ratio per 10% 1.84 [95% CI, 1.3–2.7] P =0.002), and patients with hemorrhagic transformation spent more time above the upper limit of autoregulation (10.9% versus 16.0%, P =0.042). Although there appeared to be a nonsignificant trend towards worse outcome with increasing time above systolic BP thresholds of 140 mm Hg and 160 mm Hg, the effect sizes were smaller compared with the personalized approach. Conclusions—: Noninvasive determination of personalized BP thresholds for stroke patients is feasible. Deviation from these limits may increase risk of further brain injury and poor functional outcome. This approach may present a better strategy compared with the classical approach of maintaining systolic BP below a predetermined value, though a randomized trial is needed to determine the optimal approach for hemodynamic management. Abstract : Supplemental Digital Content is available in the text.